The Control of Land Rent in the Fortified Farming Town - John Hartwick (Queen's University, Department of Economics, 2006)
We consider costly administration at the center of a farming community surrounding a fortified village. Land rent taxation is high cost mode of financing central administration in a tax incidence sense. Participatory administration by the governed is a lower cost alternative. We speculate why the low cost option has been out-competed by its higher cost alternative throughout history. We also take up constraints on predation on farmers by a landlord at the center.
Keywords: H41; H11; 330; administrative structure; public goods; welfare cost